Comparative Effectiveness of Prestroke Aspirin on Stroke Severity and Outcome. Issue 4 (19th February 2016) - Park, Jong‐Moo; Kang, Kyusik; Cho, Yong‐Jin; Hong, Keun‐Sik; Lee, Kyung Bok; Park, Tai Hwan; Lee, Soo Joo; Ko, Youngchai; Han, Moon‐Ku; Lee, Jun; Cha, Jae‐Kwan; Kim, Dae‐Hyun; et al.
Abstract : Objective: The effect of prestroke aspirin use on initial severity, hemorrhagic transformation, and functional outcome of ischemic stroke is uncertain. Methods: Using a multicenter stroke registry database, patients with acute ischemic stroke of three subtypes (large artery atherosclerosis [LAA], small vessel occlusion [SVO], or cardioembolism [CE]) were identified. NIH stroke scale (NIHSS) and hemorrhagic transformation at presentation and discharge modified Rankin Scale (mRS) were compared between prestroke aspirin users and nonusers. Results: Among the 10, 433 patients, 1, 914 (18.3%) reported prestroke aspirin use. On crude analysis, initial NIHSS scores of aspirin users were higher than nonusers (mean difference: 0.35; 95% confidence interval [CI]: 0.04–0.66). However, a multivariable analysis with an application of inverse probability of treatment weighting based on a propensity score of prestroke aspirin, having an interaction effect of prestroke aspirin use and stroke subtype in the model, showed less stroke severity for aspirin users in LAA, but not in SVO and CE than for nonusers; mean difference in NIHSS scores in LAA was –0.97 (95% CI: –1.45 to –0.49). With respect to hemorrhagic transformation and mRS, no significant interaction effects were found. Prestroke aspirin use increased the risk of hemorrhagic transformation (adjusted odd ratio: 1.34; 95% CI: 1.05–1.73), but decreased the odds of the higher discharge mRS (0.86; 0.76–0.96). Interpretation: Prestroke aspirin use may reduce initial stroke severity in atherothrombotic stroke and can improve functional outcome at discharge despite an increase of hemorrhagic transformation irrespective of stroke subtype. Ann Neurol 2016;79:560–568